Pemodelan Numerik Aliran Angin di Sekitar Gedung Tinggi Menggunakan Metode RANS Standard K-ε dengan Program OpenFOAM - Sanjaya, Yongky; Priambodo, Doni; Sarli, Prasanti Widyasih; Setio, Herlien Dwiarti; Syariefatunnisa, Syariefatunnisa (MEDIA KOMUNIKASI TEKNIK SIPIL, 2022)
Amplified wind loads around buildings could induce structural failure, thus making it important to understand the behavior of fluid flow between buildings. In this study, the analysis is performed using RANS, a computational fluid dynamics (CFD) simulation with faster computation time compared to other methods. OpenFOAM, an open-source software, is used to run the simulations. This study used a structured mesh with standard RANS k − ε turbulence model. Four symmetrical buildings with a scale of 1: 420 are used as the model of this study. Numerical modelling of different computational domain size and different degrees of fineness of the meshing is simulated to determine margin of errors. The result indicates that changes in computational domain has a significant effect on CFD analysis in lowering the error value in area with high flow speed ratio (U/U0> 1) to reach the acceptable error limit. Contrastingly, changes in the degree of fineness of the meshing do not give a significant change in error value. A relatively coarse meshing with fast computation time could give a similar result as A fine meshing model with longer computation time.